Challenges and Best Practices Solution of Agile Project Management in Public Sector: A Systematic Literature Review - Puja Putri Abdullah; Teguh Raharjo; Bob Hardian; Tiarma Simanungkalit (JOIV : International Journal on Informatics Visualization, 2023)
Applying Agile methodologies in the public sector is nothing new. In recent years, governments worldwide have moved towards Agile development, especially with the Pandemic that requires governments to move and make decisions quickly. However, the difference between the government system and the private sector, such as holding the principle of a hierarchy of authority, still challenges Agile application. This study aims to explore challenges and provide solutions for applying Agile project management in the public sector by conducting a systematic literature review (SLR) using the PRISMA method. The literature used in the SLR was obtained from four paper databases, namely Scopus, IEEE Xplore, ACM, and Emerald Insight. Five hundred ninety-five papers were found, and 18 suitable papers were obtained, which were then analyzed and obtained a total of 43 challenging issues. Each of these issues is grouped based on eight project performance domains of PMBOK 7th edition, and the solution for each challenge is obtained from the mapping results from the SLR papers and PMBOK 7th edition Guide. The results showed that the most issues were in the Development Approach and Lifecycle and Project Work domain categories, with 8 issues each. Followed by Team with 7 issues, Stakeholder with 6 issues, Delivery with 5 issues, Measurement with 4 issues, Planning with 3 issues, and Uncertainty with 2 issues. This research can be useful for academics or practitioners as a reference in facing the challenges of implementing Agile project management in the public sector